A case of Warthin tumors that were suspected to be lymph node metastases of maxillary gingival cancer. Issue 4 (July 2020) - Sato, Kotaro; Hayashi, Yasushi; Watanabe, Kazuyo; Hibi, Hideharu
Abstract: Warthin tumor is a type of salivary gland tumor that occurs mainly in the parotid gland. Warthin tumors rarely occur in multiple regions and simultaneously with oral cancer. We report a case of Warthin tumors that were suspected to be lymph node metastases of maxillary gingival cancer. In early May 2011, a 56-year-old man visited our department because of pain in the gingiva of the upper right jaw. We performed a biopsy of the lesion, and the diagnosis was squamous cell carcinoma (SCC). In early June, we started concurrent chemoradiation therapy (CCRT). We confirmed swelling of the lymph nodes with CT and MRI images and a high standard uptake value (SUV) around the right submandibular lymph nodes and superior internal jugular lymph node on FDG-PET images. However, swollen lymph nodes are not typical manifestations of metastasis; therefore, we applied radiotherapy to only the primary tumor and planned to perform neck dissection after CCRT. According to CT images after CCRT, the size of the primary tumor had drastically changed; however, there was no change in the lymph nodes. Therefore, we performed right total neck dissection as planned. We submitted several lymph nodes for diagnosis, and Warthin tumors were detected in these lymph nodes. As there were no malignancies in the other samples, metastasis was excluded. In the eight years since the patient's first visit, no SCC or Warthin tumor recurrence has been observed. This case demonstrates that salivary gland tumors can mimic metastases.